2021
DOI: 10.1039/d1ja00070e
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity improvement of solution cathode glow discharge-atomic emission spectrometry by using refrigerating anodes for optical determination of metal elements

Abstract: Sensitivity and stability improvement by reducing the metal anode temperature for metal element detection using SCGD-AES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Improvement in LOD was particularly significant for elements with atomic emission concentrated near the liquid cathode surface. Zheng et al 51 suggested a refrigerated anode to improve the analytical performance of SC-GD-OES. The spectral characteristics of metal anodes at different temperatures were studied in the range from 10 to 30 °C and the spectral emission signals of metals were found to be enhanced at lower anode temperatures during the plasma discharge.…”
Section: Liquids Analysismentioning
confidence: 99%
“…Improvement in LOD was particularly significant for elements with atomic emission concentrated near the liquid cathode surface. Zheng et al 51 suggested a refrigerated anode to improve the analytical performance of SC-GD-OES. The spectral characteristics of metal anodes at different temperatures were studied in the range from 10 to 30 °C and the spectral emission signals of metals were found to be enhanced at lower anode temperatures during the plasma discharge.…”
Section: Liquids Analysismentioning
confidence: 99%
“…These methods include electrochemical methods, glow discharge methods, inductively coupled plasma atomic emission spectrometry, uorescence analysis, and liquid chromatography. However, these techniques oen come with drawbacks such as complex sample pre-treatment requirements, limited detection capabilities, high costs, and difficult operation, [5][6][7][8][9] and are not suitable for quantitative analysis and detection of metal elements in aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of SC-GD-OES for the detection of a number of metals was improved using a refrigerating anode method. 44 Spectral characteristics of metal anodes at different temperatures were studied in the range from 10 to 30 C. The spectral signals of metals were enhanced by reducing the metal anode temperature during the plasma discharge. Use of the refrigerating anode was also observed to improve the emission stability.…”
Section: Sample Introductionmentioning
confidence: 99%